Roles of Drosophila Hox Genes in the Assembly of Neuromuscular Networks and Behavior - Joshi, Rohit; Sipani, Rashmi; Bakshi, Asif (Frontiers in Cell and Developmental Biology, 2022)
Hox genes have been known for specifying the anterior-posterior axis (AP) in bilaterian body plans. Studies in vertebrates have shown their importance in developing region-specific neural circuitry and diversifying motor neuron pools. In Drosophila, they are instrumental for segment-specific neurogenesis and myogenesis early in development. Their robust expression in differentiated neurons implied their role in assembling region-specific neuromuscular networks. In the last decade, studies in Drosophila have unequivocally established that Hox genes go beyond their conventional functions of generating cellular diversity along the AP axis of the developing central nervous system. These roles range from establishing and maintaining the neuromuscular networks to controlling their function by regulating the motor neurons' morphology and neurophysiology, thereby directly impacting the behavior. Here we summarize the limited knowledge on the role of Drosophila Hox genes in the assembly of region-specific neuromuscular networks and their effect on associated behavior.